Basic anthropomorphological characteristics of elite senior Serbian water polo players according to field position - Dopsaj, M.; Aleksandrovic, M. (International Journal of Fitness, 2009)
The aim of this research is to define basic anthropomorphological characteristics of top senior water polo players according to field position. Thirty-one waterpolo players participated in the research and they were all Serbian national team members (ex Serbia and Montenegro) selected according to the following structure related to their field position: 1. Goalkeepers (N=6), 2. Perimetal players (left and right wing, and left and right guard) (N=13), 3. Centre defenders (N=6), and 4. Centre forewards (N=6). The parameters which were used to evaluate basic anthropomorphological characteristics of water polo players were: BH - Body Height (cm), BM - Body Mass (kg), BMI - Body Mass Index (kg/m2), and BSA - Body Surface Area (cm2). The results have shown that there is a statistically significant difference between the estimated variables in the function of player`s position in the tested sample (Wilk`s Lambda = 0.432, Fratio =1.983, p value = 0.041), in BM, BH and BSA at the level: Frelation = 3.97, p value = 0.018, Frelation = 6.10, p value = 0.003 i Frelation = 5.03, p value = 0.007, respectively. Generally speaking, we can conclude that it is important to choose those players who are taller, while the appropriate values of body mass, and body mass index can be formed during the final phase of growth (18 - 20 years of age), even at the senior age (after 20 years of age).